2015
DOI: 10.1155/2015/345764
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Open Globe Injuries and Correlation of Ocular Trauma Score in Tianjin, China

Abstract: Purpose. To investigate prognostic factors that influence the final visual acuity (VA) and to correlate the ocular trauma score (OTS) with the final VA in open globe injuries. Methods. A retrospective review of 298 patients with open globe injuries admitted to Tianjin Medical University General Hospital was carried out from January 1, 2010, till December 31, 2014. Prognostic factors influencing the final VA in patients with open globe injuries and the correlation between OTS and the final VA were examined. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
50
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 33 publications
16
50
3
4
Order By: Relevance
“…For the young-adult and middle-aged males in our study, activity risk factors for major ocular trauma were metal-working, driving, social behaviours such as fighting, and participation in dangerous sports or hobbies, similar to findings from previous reports 7 , 8 , 11 14 , 17 , 19 . In contrast, women in our study were most often injured at home and the workplace.…”
Section: Discussionsupporting
confidence: 90%
“…For the young-adult and middle-aged males in our study, activity risk factors for major ocular trauma were metal-working, driving, social behaviours such as fighting, and participation in dangerous sports or hobbies, similar to findings from previous reports 7 , 8 , 11 14 , 17 , 19 . In contrast, women in our study were most often injured at home and the workplace.…”
Section: Discussionsupporting
confidence: 90%
“…Those eyes with final VA of NLP all occurred in cases with initial VA of LP/HM or worse. Meng and Yan [27] have demonstrated that initial VA was found to correlate significantly with final VA in eye injuries. Our study showed the same result that initial VA correlated with final VA (Spearman's test, r = 0.703, p = 0.001), which was consistent with that of Man and Steel [28] and Weichel et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Relative pupillary afferent defect is used to calculate the ocular trauma score and has been also shown among the factors suggesting unfavourable visual outcome in children as well as in adult population in open globe injuries [ 26 28 ]. However, it is difficult to show the presence of relative pupillary defect in young children as it is difficult to cooperate during examination.…”
Section: Discussionmentioning
confidence: 99%